Paper wishes - Sepahban, Lois (Farrar, Straus, Giroux, 2016)
Near the start of World War II, young Manami, her parents, and Grandfather are evacuated from their home and sent to Manzanar, an ugly, dreary internment camp in the desert for Japanese-American citizens.